1974
DOI: 10.1039/f29747001978
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated potassium zincate solutions studied using laser Raman spectroscopy and potentiometry

Abstract: The results of a study of the nature of concentrated potassium zincate solutions in alkali are reported. Data from several independent but complementary techniques are mutually consistent and show that electrolytically produced solutions of high concentration are relatively complex, the complexity depending upon the age. It is concluded that initially quasi-colloidal particles, based on Zn(OH), and molecules of solvation, are present. The particles of colloidal character are electroinactive and undergo a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…11 The precipitation rate is rather slow below this critical concentration. 12 Concentration dependence of refractive index.-The concentration dependence of refractive index of Zn͑OH͒ 4 2− ion was measured and could be expressed by the following linear approximation…”
Section: Resultsmentioning
confidence: 97%
“…11 The precipitation rate is rather slow below this critical concentration. 12 Concentration dependence of refractive index.-The concentration dependence of refractive index of Zn͑OH͒ 4 2− ion was measured and could be expressed by the following linear approximation…”
Section: Resultsmentioning
confidence: 97%
“…Figure 3 shows the transient variation in calculated anode surface concentrations of both Zn(OH) 4 2− and OH − ions at x = 0.1, 4, and 7.9 mm along the Zn anode at i ave = 20 mA/cm 2 in 1.95 M KOH electrolyte. The solubility limits are also shown in Figure 3a, which are estimated as a function of bulk electrolyte concentration according to Briggs et al 28 In Figure 3, the concentrations of zincate ion and hydroxide ion are nearly identical for x = 0.1 and x = 4 because the influence of hydroxide ion concentration changes at the positive electrode is small at 0 < x ≤ 4.…”
Section: Physical and Mathematical Modelingmentioning
confidence: 97%
“…28 An important problem is determining how to estimate the critical concentration of Zn(OH) 4 2− ion, either numerically or experimentally. The holographic interferometry technique might provide such information at a geometrically flat electrode surface.…”
Section: Physical and Mathematical Modelingmentioning
confidence: 99%
“…The transient variations of anode surface concentrations of both Zn(OH) 4 2-and OH -ions are calculated at x=0.1, 4, 7.9 mm along a Zn anode at i ave =20 mA/cm 2 in 1.95 M KOH electrolyte. Briggs et al reported that the chemical solubility limit is 0.14 M, while the electrochemical solubility limit is 0.47 M in a 10wt % (1.95 M) KOH electrolyte (22). Zincate ion concentration at the surface electrode increases sharply as time progresses.…”
Section: Comparing With Experimental and Calculated Resultsmentioning
confidence: 99%